Assessment of Eco-geomorphological potential of Mongolia - Bumtsend, Bayanjargal; Munkhtur, Purevsuren; Erdenedalai, Avirmed (Proceedings of the Mongolian Academy of Sciences, 2020)
The eco-geomorphological analysis includes the impact assessment of relief under various ecosystem conditions in as much relief has various ecological roles, both direct and indirect. Rising elevation above sea level is mostly influenced by climate indirectly leading to reduced air pressure, oxygen deficiency, reduction of air temperature, excessive solar radiation, and creation of strong wind. The depth of relief dissection of the bumpy surface of mountainous areas created by floods and mudflows, and the depth of the bumpy surface increases energy consumption and poses risks during mountain climbing, and also has negative economic implications if economic activities are undertaken in such terrain. On the other hand, mountainous landscapes have a specific impact on human well-being and also have considerable potential for promoting tourism. Although, in the steppe environment, relief dissection increases the unique features of the landscape and increases the potential of tourism in other respects, however, it is assessed negatively to a large extent. The nature of corelationship between and the interdependence of the terrestrial surface and population, terrestrial surface and livestock, terrestrial surface and agriculture, which are significant in the study into the inter-relationship between environment and human society, was assessed and determined , and the relevant conclusion was drawn.